2018
DOI: 10.1126/sciadv.aas9459
|View full text |Cite
|
Sign up to set email alerts
|

Toward digitally controlled catalyst architectures: Hierarchical nanoporous gold via 3D printing

Abstract: Digitally controlled catalyst architectures via 3D printing potentially revolutionize the design of chemical plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
127
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 41 publications
1
127
0
1
Order By: Relevance
“…In a similar manner, Biener et al. demonstrated the 3D printing of a hierarchical porous gold monolith. An Ag–Au composite ink composed of Ag and Au clays and melaleuca alternifolia (tea tree) leaf oil was 3D printed into a lattice cube.…”
Section: Advanced Materials Fabricated By Diwmentioning
confidence: 94%
See 1 more Smart Citation
“…In a similar manner, Biener et al. demonstrated the 3D printing of a hierarchical porous gold monolith. An Ag–Au composite ink composed of Ag and Au clays and melaleuca alternifolia (tea tree) leaf oil was 3D printed into a lattice cube.…”
Section: Advanced Materials Fabricated By Diwmentioning
confidence: 94%
“…By using the hierarchical co-assembly-enhanced DIW method, we have successfully fabricatedh ierarchically porous 3D silica monoliths and fluorescent organosilica lattices. [76] In as imilarm anner,B iener et al demonstrated [122] the 3D printing of ah ierarchical porous gold monolith. An Ag-Au composite ink composed of Ag and Au clays and melaleuca alternifolia (tea tree) leaf oilw as 3D printed into al attice cube.…”
Section: Hierarchically Ordered Materialsmentioning
confidence: 99%
“…In this way, Ag foams with a density down to 1.3 mg cm −3 and an electrical conductivity of up to 1.3 S cm −1 were obtained. In another recent work, Zhu et al presented a combined 3D printing with a dealloying approach. The initial thixotropic Au–Ag composite inks were prepared by mixing Ag clay, Au clay (metal powders, water, and organic binders), and an organic solvent, which were then printed to form a desired architecture.…”
Section: Fabrication Strategiesmentioning
confidence: 99%
“…Despite these advances, the pursuit of exceedingly small pores to obtain high specific surface area restricts mass transport in nanoporous metal. Recent studies have centered on the development of hierarchically porous metals, which have combined macro‐ and meso‐porosity that promotes fast mass exchange . A hierarchical structure with nano‐ to macro‐scaled pore sizes can indeed be utilized for smooth mass transport combined with a large specific surface area.…”
mentioning
confidence: 99%
“…In contrast to these conventional methods, it has recently been reported that hierarchical nanoporous gold can be fabricated by 3D printing using Au and Ag “inks” and chemical dealloying. Pores with controlled sizes between 30 nm and 1000 µm can markedly improve mass transport and reaction rates . This combination of techniques provides an alternative route for obtaining complex hierarchical structures.…”
mentioning
confidence: 99%